1992
DOI: 10.1111/j.1744-7348.1992.tb03437.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance pattern of downy mildew resistance in advanced generations of sorghum*

Abstract: Inheritance pattern of downy mildew resistance in 4 advanced generations of sorghum* 'JA# 1195 \07/' By BELUM V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 2 publications
0
11
0
2
Order By: Relevance
“…Genetic variation for resistance to this pathogen has also been reported [112][113][114]. Multiple races of downy mildew that infect sorghum have been identified and, consequently, resistance genes have come from multiple sources [113].…”
Section: Breeding For Stress Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variation for resistance to this pathogen has also been reported [112][113][114]. Multiple races of downy mildew that infect sorghum have been identified and, consequently, resistance genes have come from multiple sources [113].…”
Section: Breeding For Stress Tolerancementioning
confidence: 99%
“…Resistance to single races of this pathogen is reported as simply inherited and, therefore, resistance to the pathogen in general is described as oligogenic in most cases [115]. For example, resistance to the ICRISAT Centre race has been described as fitting the expected ratio of a two locus model with complementary and inhibitory interactions [114]. Thus, it is feasible to pyramid resistance genes for multiple races as new ones are identified.…”
Section: Breeding For Stress Tolerancementioning
confidence: 99%
“…Alguns pesquisadores propuseram a hipótese de que a linhagem de sorgo QL-3, resistente às três raças identificadas no Texas, possui dois genes dominantes condicionando resistência, enquanto a linhagem SC414-12, possui um ou dois genes dominantes controlando a resistência às três raças (Craig & Schertz, 1985;Sifuentes & Frederiksen, 1988;Reddy et al, 1992). Em trabalho realizado anteriormente na �ndia, concluiu-se que a resistência da cultivar QL3 era condicionada por 6 genes (Bhat, 1981).…”
Section: Genética E Herança Da Resistênciaunclassified
“…A further study by Reddy et al, (1992) also found resistance in QL-3 was dominant over susceptibility; a two-locus model with independent segregation and a combination of complementary and inhibitory interallelic interaction explained the inheritance pattern they observed. However, most resistance in sorghum is presumed to be monogenic, some possibly oligogenic, which implies a threat of resistance breaking down (Craig and Odvody, 1992).…”
Section: Inheritance Of Resistance To Sorghum Downy Mildewmentioning
confidence: 99%
“…Nevertheless in two crosses additive gene effect was also significant in addition to dominant gene effect (Krishnappa et al, 1995). Susceptibility to SDM infection was found to be partially dominant over resistance and resistance to SDM controlled by polygenes where as in sorghum resistance to SDM was found to be dominant (Reddy et al, 1992). No attempt has been reported in maize regarding number of genes involved for resistance to SDM using a chi-square test so far.…”
Section: Inheritance Of Resistance To Sorghum Downy Mildewmentioning
confidence: 99%